Economic Evaluation of Early Psychosis Interventions From A Canadian Perspective. (October 2022) - Tarride, Jean-Eric; Blackhouse, Gord; Abdel-Baki, Amal; Latimer, Eric; Mulvale, Gillian; Cooper, Brian; Langill, Gord; Milinkovic, Deborah; Stennett, Rosain; Hurley, Jeremiah
Background: Compared to treatment as usual (TAU), early psychosis intervention programs (EPI) have been shown to reduce mortality, hospitalizations and days of assisted living while improving employment status. Aims: The study aim was to conduct a cost-benefit analysis (CBA) and a cost-effectiveness analysis (CEA) to compare EPI and TAU in Canada. Methods: A decision-analytic model was used to estimate the 5-year costs and benefits of treating patients with a first episode of psychosis with EPI or TAU. EPI benefits were derived from randomized controlled trials (RCTs) and Canadian administrative data. The cost of EPI was based on a published survey of 52 EPI centers in Canada while hospitalizations, employment and days of assisted living were valued using Canadian unit costs. The outcomes of the CBA and CEA were expressed in terms of net benefit (NB) and incremental cost per life year gained (LYG), respectively. Scenario analyses were conducted to examine the impact of key assumptions. Costs are reported in 2019 Canadian dollars. Results: Base case results indicated that EPI had a NB of $85, 441 (95% CI: $41, 140; $126, 386) compared to TAU while the incremental cost per LYG was $26, 366 (95% CI: EPI dominates TAU (less costs, more life years); $102, 269). In all sensitivity analyses the NB of EPI remained positive and the incremental cost per LYG was less than $50, 000. Conclusions: In addition to EPI demonstrated clinical benefits, our results suggest that large-scale implementation of EPI in Canada would be desirable from an economic point of view .